QUO VADIS RT RW - Survianto, Eko (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Local Neighbourhood Associations (RT/RW) have sociohistorically passed several regimes and eras. Up to now, they still exist as main institutions within communities. Centralized policy during the new order era has made RT/RWs as parts of governmental bureaucracy. The image remains the same until now. Despite the grassroot organization perspective that RT/RWs are structurally a model of grassroot conservatism, they culturally and functionally may transform themselves intoservice units. Reform movement has given them way to be more independent and self-reliant in providing services for their own communities. The wind of change is of course at the hand of the local governments.